1991
DOI: 10.1021/jo00004a047
|View full text |Cite
|
Sign up to set email alerts
|

Concerning the mechanism of reaction of lithium aluminum hydride with alkyl halides

Abstract: A detailed study of the mechanism of reaction of LiAlH4 with alkyl halides has been carried out with special emphasis on thé use of radical probes. The data presented strongly support the validity of using radical probes in this reaction as an indication of an electron-transfer process. These studies also suggest a radical chain process (hydrogen atom transfer) in addition to the halogen atom transfer process on which we reported earlier. Studies to determine the influence of impurities as well as a potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…18 This procedure makes the preparation simpler but still requires the extraction of the aminealane complex from LAH under an inert atmosphere. Reports that AlH 3 is formed as a by-product of the reduction of an alkyl halide with LAH 19,20 and that AlH 3 generated in this way reduced ethyl a-(hydroxymethyl)acrylate to a-(hydroxymethyl)acrolein 21 were little noted, 22 as evident from the continued usage of 100% H 2 SO 4 and LAH to generate AlH 3 , e.g., in the total synthesis of (AE)-gelsemine. 23 In this paper we show that the HWE reaction of a variety of aldehydes with triethyl phosphonoacetate in the presence of K 2 CO 3 in H 2 O-2-PrOH (1 : 1) produced (E)-a,b-unsaturated esters with convenience and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…18 This procedure makes the preparation simpler but still requires the extraction of the aminealane complex from LAH under an inert atmosphere. Reports that AlH 3 is formed as a by-product of the reduction of an alkyl halide with LAH 19,20 and that AlH 3 generated in this way reduced ethyl a-(hydroxymethyl)acrylate to a-(hydroxymethyl)acrolein 21 were little noted, 22 as evident from the continued usage of 100% H 2 SO 4 and LAH to generate AlH 3 , e.g., in the total synthesis of (AE)-gelsemine. 23 In this paper we show that the HWE reaction of a variety of aldehydes with triethyl phosphonoacetate in the presence of K 2 CO 3 in H 2 O-2-PrOH (1 : 1) produced (E)-a,b-unsaturated esters with convenience and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…H-Atom abstraction by 6 from the polyether solvent provides a plausible mechanistic pathway for the formation of 4. Indeed, anthracene was used as trap for radical anions in mechanistic studies investigating the involvement of SET processes [6]. Takikawa et al demonstrated that a SET process was involved in the reaction of benzenethiol (7) with 9-nitroanthracene [7].…”
Section: The Reaction Of 9-bromoanthracene With Benzenethiolate Anion Inmentioning
confidence: 99%
“…We initiated our synthetic efforts by studying the conjugate addition of cuprate reagents derived from known neopentyl iodide 12a to enone (±)- 5 , to mimic the eventual cyclopentyl cuprate that would be required for tricyclic analogs (Scheme ). However, several problems quickly surfaced including the anticipated low reactivity of the neopentyl cuprate reagent which could be overcome by forming the more reactive higher order organocuprate using the method of Lipshutz .…”
mentioning
confidence: 99%
“…However, several problems quickly surfaced including the anticipated low reactivity of the neopentyl cuprate reagent which could be overcome by forming the more reactive higher order organocuprate using the method of Lipshutz . Unfortunately, the resulting cuprate was prone to 5-exo-trig cyclization (see inset, Scheme ), , likely accelerated by the Thorpe–Ingold ( gem -dimethyl) effect. This side reaction is unavoidable even at −78 °C unless the olefin is trisubstituted, directing us toward a defensive strategy and the use of iodide 13 bearing a pendant trisubstituted alkene known to lower the rate of intramolecular cyclization .…”
mentioning
confidence: 99%